The Influence of Tourist Attractions, Government Support, and Muslim-Friendly Tourism Services on Increasing the Income of the Harian District Community in Samosir Regency - Hasibuan, Nurul Rizkia; Qarni, Waizul; Atika, Atika (SENTRALISASI, 2026)
This study aims to analyze the influence of Tourist Attractions, Government Support, and Muslim-Friendly Tourism Services on increasing community income in Harian District, Samosir Regency. The research adopts a quantitative approach using a survey method, with data collected from 70 respondents selected through purposive sampling. Data were analyzed using multiple linear regression to examine both partial and simultaneous effects of the independent variables. The findings reveal that Tourist Attractions and Government Support have a positive and significant effect on community income (p < 0.05), while Muslim-Friendly Tourism Services also contribute positively as a differentiation strategy in attracting tourists and increasing local spending. Simultaneously, the three variables significantly affect community income, as indicated by the F-test (p < 0.05). The model explains 47.6% of the variance in community income (R² = 0.476; Adjusted R² = 0.452), indicating a moderate explanatory power. The novelty of this study lies in integrating Muslim-friendly tourism services into the Local Economic Development (LED) framework, highlighting its role not only as a cultural-religious attribute but also as an economic driver that enhances community income. These findings imply that optimizing tourism potential through targeted government support and service differentiation is essential for promoting inclusive local economic growth and improving community welfare.